PSYCHOLOGICAL RESILIENCE IN OLDER U.S. VETERANS: RESULTS FROM THE NATIONAL HEALTH AND RESILIENCE IN VETERANS STUDY - Pietrzak, Robert H.; Cook, Joan M. (Depression and anxiety, 2013)
Background Although a large body of empirical research has examined negative psychological outcomes in older veterans, relatively little is known about the prevalence and determinants of psychological resilience in this population. Methods A nationally representative sample of 2,025 U.S. veterans aged 60 and older (mean = 71.0, standard deviation = 7.1, range = 60–96) completed a web‐based survey as part of the National Health and Resilience in Veterans Study (NHRVS). Cluster analysis of measures of lifetime potentially traumatic events, and current PTSD, major depression, and generalized anxiety symptoms was used to classify psychological outcomes. Results A three‐group solution best fit the data: Control (low number of lifetime traumas, low current psychological distress; 60.4%); Resilient (high number of lifetime traumas, low current psychological distress; 27.5%); and distressed (high number of lifetime traumas, high current psychological distress; 12.1%). Among older veterans with a high number of traumas, 69.5% were in the Resilient group. Compared to the Distressed group, the Resilient group was more likely to have college or higher level of education, and to be married or living with a partner. They also scored higher on measures of emotional stability, social connectedness (i.e., secure attachment style, social support), protective psychosocial characteristics (e.g., community integration, purpose in life), and positive perceptions of the military's effect on one's life; and lower on measures of physical health difficulties and psychiatric problems, and openness to experiences. Conclusions Among older U.S. veterans who have endured a high number of traumas in their lifetimes, nearly 70% are psychologically resilient in later life. Prevention efforts targeted toward bolstering social connectedness, community integration, and purpose in life may help promote psychological resilience in older veterans who endured a significant number of traumas in their lives.